1983
DOI: 10.1002/ana.410130209
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline potentiates morphine analgesia by a direct action on the central nervous system

Abstract: Trycyclic antidepressants are often effective in the management of neuropathic pains. To elucidate the mechanism of tricyclic-induced analgesia, amitriptyline and other drugs were injected into lightly anesthetized rats either systemically or via lumbar intrathecal cannulas. Analgesia was assessed by measuring the latency of the tail flick reflex. Using this model, intrathecal amitriptyline (30 micrograms) significantly enhanced the analgesic effect of an intraperitoneal dose of morphine (0.5 mg/kg) that by it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
64
0
9

Year Published

1984
1984
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(76 citation statements)
references
References 30 publications
3
64
0
9
Order By: Relevance
“…Monoamine reuptake inhibitors can enhance the antinociception produced by systemic opioids. 95,96 Intrathecally administered anticholinesterases, such as neostigmine, can produce potent analgesia 97 and can synergistically enhance the antinociception of both morphine and clonidine. 98,99 Acetylcholinesterases appear to exert their analgesic action through a muscarinic, as opposed to a nicotinic, action (muscarinic agonists, but not nicotinic agonists, are analgesic when injected intrathecally).…”
Section: Nmda Receptor Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoamine reuptake inhibitors can enhance the antinociception produced by systemic opioids. 95,96 Intrathecally administered anticholinesterases, such as neostigmine, can produce potent analgesia 97 and can synergistically enhance the antinociception of both morphine and clonidine. 98,99 Acetylcholinesterases appear to exert their analgesic action through a muscarinic, as opposed to a nicotinic, action (muscarinic agonists, but not nicotinic agonists, are analgesic when injected intrathecally).…”
Section: Nmda Receptor Antagonistsmentioning
confidence: 99%
“…98,99 Acetylcholinesterases appear to exert their analgesic action through a muscarinic, as opposed to a nicotinic, action (muscarinic agonists, but not nicotinic agonists, are analgesic when injected intrathecally). 100,101 Amitryptiline, a tricyclic antidepressant, can enhance the antinociceptive effects of systemic opioids 96 and of intrathecal neostigmine. 98 Potassium channel openers, such as diazoxide and minoxidil, have also been shown to produce antinociception when administered intrathecally.…”
Section: Nmda Receptor Antagonistsmentioning
confidence: 99%
“…Although tolerance may be seen at the level of the receptor and its second-messenger system (3)(4)(5)(6)(7)(8)(9)(10)(11), some evidence suggests that morphine tolerance is mediated, in part, through activation of antagonistic systems and/or a down-regulation of facilatory ones (12)(13)(14)(15)(16)(17). However, cholecystokinin antagonists and antidepressants active against tolerance also potentiate morphine analgesia in naive animals as well, indicating that their actions are not directed specifically against tolerance.…”
mentioning
confidence: 99%
“…2A for 9 days. On the 10th day the group received a single injection of NO2Arg followed 15 min later by the challenge morphine dose. NO2Arg (i.p.)…”
mentioning
confidence: 99%
“…Different studies have demonstrated that tolerance to depressant effects develops (Martin et al 1963) and analgesic effects of opiates in rodents Mayer et al 1995). Antidepressants have been reported to enhance opioid analgesia (Botney & Fields 1983). Sierralta et al (1995) reports that the antinociceptive activity of antidepressants could partly depend on their interaction with opioid receptors in CNS.…”
mentioning
confidence: 99%